Visual Outcome of Ocular Trauma in Patients Managed at Tertiary Care Hospital - Bilal, Muhammad; Tariq, Muhammad; Shah, Shafqat Ali; Ali, Ammad; Ali, Saad; Ayub, Muhammad (Journal of Gandhara Medical and Dental Science, 2021)
OBJECTIVES: To determine the visual outcome of ocular trauma in patients admitted in the ophthalmology unit. METHODOLOGY: This descriptive cross sectional study was conducted after approval of ethical committee, from June 2017 till June 2019 at Ophthalmology Department, Medical Teaching Institution, Mardan Medical Complex, Mardan (MTI-MMC). A total of 501 patients of either gender having ocular trauma were enrolled in study. Following informed written consent, detailed history, ocular examination and investigations the surgical procedure was carried out. A pre-designed proforma was used to record the outcome along with demographics and type of trauma, which was analyzed using SPSS V-24.0. RESULTS: In a total of 501 patients the mean age of sample was 30.5±2.2. Among 501, males were 408 (81.44%) and female were 93 (18.56%) with ratio of 9:1. Ocular trauma was more common in age of <15 year with 174 (34.73%) patients. Professional injuries were more common and observed in 306 (61%) patients as compared to non-professional injuries in 195 (38%). Penetrating trauma occurred in 276 (55.08%) patients, which was higher than blunt 144 (28.74%) and perforating trauma 81 (16.16%). Good visual outcome was observed in 308 (61.47%), poor in 172 (34.33%) and blindness in 21 (4.1%) patients. CONCLUSION: The study concludes a better visual outcome for ocular traumas after surgical procedures. Young males were found to be more prone for traumatic injuries, in which professional and penetrating trauma leads the chart.